Saturday

March 28, 2015

March 28, 2015

Posted by **kris** on Tuesday, August 29, 2006 at 12:42pm.

y=(x+a) ^3+ 2

10= (3+ a) ^3 + 2

10-2= (3+ a) ^3 + 2-2

8= (3+ a) ^3

Take the cube root of each side...

2= 3-a solve for a

So I went like this:

2-2+a= 3-a-2+a

a= 1

So the new equation would be? I am unsure which equation do I put it in for?

8= (3+ a) ^3

Take the cube root of each side...

2= 3-a solve for a ****Nope, you changed the sign on a. 1=3+a, a=-1

The new equation is

y=(x-1)^3 +2 This shifts the equation along the horizontal axis to the right.

**Answer this Question**

**Related Questions**

help! - A horizontal translation is applied to the graph of y= X^ 3 + 2 so that ...

Math help Please - 2. How do the graphs of y = 1/x and y = 3/x – 4 compare? (1 ...

Plz Help!Algebra!!! - Choose the description of the graph of the equation x = -8...

Math - The graph of y = f (x) = b^x, where b > 1, is translated such that the...

Algebra 2 - 2. How do the graphs of y = 1/x and y = 3/x – 4 compare? (1 point) ...

Physics: Data Analysis - Power Law - In an experiment, two variables quantities...

math - HELP Not great in these Express y=2x^2 -12x +23 in the form y=2(x-c)^2 + ...

precalculus - How do I find the vertical/horizontal compression/stretch? For the...

Precalculus - Can someone help me with this question? I got the transformation ...

Algebra--Math matePlease help - Homework Help Forum: Algebra-Please help-I'm ...